Corporate Governance and Performance Influencing Firm Value Based on Market Value of SET 100 Listed Companies in the Stock Exchange of Thailand - Meangjun, chureeporn; Thanaanawat, Pawinee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
This research aimed to examine the corporate governance including shareholder structure, board structure, directors’ compensation, and the performance factors influencing firm value based on market value, and to investigate the impact of performance on firm value based on market value among companies listed on the Stock Exchange of Thailand (SET), specifically in the SET100 group, comprising 81 companies, excluding financial businesses. The financial data from 2020 to 2023, totaling 324 firm-year observations, were analyzed using Structural Equation Modeling (SEM) and Path Analysis. The results revealed that good corporate governance, particularly in terms of shareholder structure and board structure, positively influenced both firm performance and market value. Directors’ compensation was also found to have a positive effect on firm performance and market value. Moreover, audit fees had a direct positive impact on both firm performance and market value. Finally, firm performance was shown to positively influence the market value of companies listed in the SET100 index.